The American dream : a short history of an idea that shaped a nation - Cullen, Jim (2003)
Introduction: A dream country. - Dream of the good life (I) : the Puritan enterprise. - Dream charter : The declaration of independence. - Dream of the good life (II) : upward mobility. - King of America : the dream of equality. - Detached houses : the dream of home ownership. - Dream of the good life (III) : the coast. - Conclusion: Extending the dream